2021
DOI: 10.1111/jam.15008
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on mycotic keratitis caused by dematiaceous hyphomycetes

Abstract: Dematiaceous hyphomycetes (DH) are darkly pigmented fungi ubiquitously found all over the world as plant pathogens and saprophytes, and many of the members of this group have emerged as opportunistic pathogens. These fungi are responsible for a wide variety of infections including mycotic keratitis, which is considered as one of the major causes of corneal blindness, particularly in tropical and subtropical countries with an annual global burden of about 1 000 000 patients. The infection is more common in work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…Previous studies have indicated that the most frequently associated dematiaceous species were Curvularia spp., Alternaria spp., Exserohilum spp., and Cladosporium spp. [ 22 , 23 , 24 , 25 ]. Among these species, Curvularia spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that the most frequently associated dematiaceous species were Curvularia spp., Alternaria spp., Exserohilum spp., and Cladosporium spp. [ 22 , 23 , 24 , 25 ]. Among these species, Curvularia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Among these species, Curvularia spp. was the most common cause of keratitis [ 4 , 6 , 15 , 25 , 26 ]. However, in our study, Lasiodiplodia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Other important eye-infecting genera are Aspergillus (13.0%), Purpureocillium (12.4%), Alternaria (4.7%), and Scedosporium (4.7%). Strikingly, dematiaceous genera such as Alternaria and Cladosporium contribute to a smaller extent compared to studies of tropical and subtropical regions with more intensive UV radiation [ 2 , 12 , 36 , 46 , 47 , 48 , 49 , 50 ]. Dematiaceous genera such as Bipolaris and Curvularia , which are important eye pathogens in the tropics and subtropics, were not sent to the NRZMyk.…”
Section: Discussionmentioning
confidence: 99%
“…Most filamentous fungi are saprophytic microorganisms that are found in a variety of natural habitats. Human exposure to fungus-contaminated plants or other organic matter may facilitate exogenous infections of the eye, resulting in corneal trauma [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%